FEATURES OF PHYSICAL DEVELOPMENT AND ADAPTATION CAPABILITIES OF THE CARDIORESPIRATORY SYSTEM IN CHILDREN AND TEENEGERS ENGAGED IN SWIMMING AND RHYTHMIC GYMNASTICS - Rakhmatova Fotima Utkirovna, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract. This article examines the impact of regular physical activity, including swimming  and  rhythmic  gymnastics,  on  the  cardiorespiratory  system,  physical development.  The  aim  of  this  study  is  to  analyze  the  physical  development  and functional state of the cardiorespiratory system in children and adolescents involved in swimming and rhythmic gymnastics. A review of current scientific publications on the  impact  of  systematic  physical  activity  on  anthropometric  indicators, cardiovascular  and  respiratory  performance,  of  young  athletes  is  provided.  It emphasizes the importance of developing comprehensive programs for assessing the body's  functional  reserves  to  prevent  noncommunicable  diseases  and  ensure  safe sports  activities.  A  literature  review  revealed  ambiguous  effects  of  youth  sports compared  to  physical  education  in  the  school  curriculum,  which  requires  further research.